Academic Adaptation to Remote Higher Education Questionnaire: Adaptation and Psychometric Study with Universities - Ferraz, Adriana Satico; Inácio, Amanda Lays Monteiro [UNESP]; de Oliveira Barros Bathaus, Jennifer Kerolly; dos Santos, Acácia Aparecida Angeli (FapUNIFESP (SciELO), 2023)
Due to the need to understand the academic adaptation in the temporary transition from the in-person to the virtual modality, the general objective of this research is to adapt the Academic Adaptation to Higher Education Questionnaire for remote teaching. The specific objectives are to investigate their evidence of content validity and internal structure-based validity and reliability estimates. The questionnaire was adapted for remote teaching in the first stage of the research. The questionnaire was, then, evaluated by three judges and 12 students, whose results evidenced the content validity. Subsequently, 319 students answered the questionnaire. With confirmatory factor analysis, a plausible model was identified, containing five factors (Institutional, Social, Study, Personal-Emotional, and Career Planning), indicating validity based on the internal structure. Additionally, the questionnaire showed adequate accuracy indices (ω >.85). The practical implications are traced, and we also suggest for the questionnaire to be adjusted for the hybrid teaching modality.
Keywords: college environment; college students; educational technology; higher education; psychometrics